Pelatihan Pembuatan Permainan Kuis Interaktif Online yang Keren dan Kekinian Dengan Aplikasi Quizizz - Siti Fatimah Sihotang; Zuhri Zuhri (Jurnal Pengabdian Ahmad Yani, 2021)
The ongoing COVID-19 pandemic has had a significant impact on the education section. All educators and students are affected by this pandemic. All learning processes, which are usually done face-to-face, under government recommendations, must be carried out online from home ( E-learning ) now. Thus, online-based distance learning (E-learning) is becoming more and more developed with a variety of different techniques and strategies. One form of utilizing E-Learning applications that can be used for current learning activities is Quizizz. Quizizz can be used as a solution to create interactive and fun online interactive quizzes. Quizizzhas many advantages that are very useful in motivating students to learn by using the principle of learning while playing. The purpose of this research is to assist teachers to be able to use and utilize online learning media with the support of the Quizizzapplication to create cool, contemporary, interactive and fun online interactive quizzes. The implementation method is carried out in the form of training activities for making cool and contemporary online interactive quiz games, with the participants from Alqur'an Taqarrub Kindergarten teachers, Medan. Based on these training activities, it was identified that the teachers were very enthusiastic and understood how to make their quizzes for kindergarten students by using the menu provided. Thus, it is clear that the use of the Quizizz E-Learning application can assist teachers as educators in conducting evaluations without being limited by place, an attractive appearance and regulated time settings guide students' concentration.